FAKTA POLIGAMI SEBAGAI BENTUK KEKERASAN TERHADAP PEREMPUAN: KAJIAN LINTASAN TAFSIR DAN ISU GENDER - Wely Dozan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The focus of this research is to analyze polygamy in the discourse of thought and gender issues that seen as an environment and have a detrimental impact on women.. The research approach is literature study in answering research problems through various literatures, namely books, journals, articles, and supporting references. The results of this study indicate that polygamy in the concept of gender has occurred violence against women in all actions based on differences in sex through, physical, sexual, and psychological, including on certain threats. Violence against women, especially in domestic relationships, is often referred to as gender-based violence. The study of interpretation as a solution to eliminating problems and upholding justice through a contextual interpretation and paying attention to the objectives of the Qur'an for society, namely by means of monogamy (marrying someone) and rejecting polygamy in the context of marriage. The jargon of tafsir scholars in understanding the text of the Koran, namely